2018
DOI: 10.1111/jcmm.13737
|View full text |Cite
|
Sign up to set email alerts
|

Signalling mechanisms that regulate metabolic profile and autophagy of acute myeloid leukaemia cells

Abstract: Acute myeloid leukaemia (AML) comprises a heterogeneous group of hematologic neoplasms characterized by diverse combinations of genetic, phenotypic and clinical features representing a major challenge for the development of targeted therapies. Metabolic reprogramming, mainly driven by deregulation of the nutrient‐sensing pathways as AMPK, mTOR and PI3K/AKT, has been associated with cancer cells, including AML cells, survival and proliferation. Nevertheless, the role of these metabolic adaptations on the AML pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…This opposite mechanism of action might be partially explained by the different cell models used by these studies (U937 in the first; HL60, NB4, and THP-1 in the second) that can reflect the heterogeneity in genetic and clinical features of the AML. Indeed, Pereira et al confirmed this heterogeneity by measuring glycolysis of AML cell lines in correlation with Akt/mTOR and AMPK activation status, finding a fluctuation in the glycolytic flux across the different cell lines, correlated with a different intracellular signaling [64]. Of interest, in the KG1 cell line they found a simultaneous activation of AMPK and mTOR, subverting the canonical view that dictates an antithetic role for these two kinases [64].…”
Section: Acute Myeloid Leukemiamentioning
confidence: 95%
“…This opposite mechanism of action might be partially explained by the different cell models used by these studies (U937 in the first; HL60, NB4, and THP-1 in the second) that can reflect the heterogeneity in genetic and clinical features of the AML. Indeed, Pereira et al confirmed this heterogeneity by measuring glycolysis of AML cell lines in correlation with Akt/mTOR and AMPK activation status, finding a fluctuation in the glycolytic flux across the different cell lines, correlated with a different intracellular signaling [64]. Of interest, in the KG1 cell line they found a simultaneous activation of AMPK and mTOR, subverting the canonical view that dictates an antithetic role for these two kinases [64].…”
Section: Acute Myeloid Leukemiamentioning
confidence: 95%
“…In addition, Akt interacts with PDK1, influencing the entrance of pyruvate into the mitochondrial metabolism [77]. Akt may also affect oxidative phosphorylation; it was shown that Akt could promote an indirect oxidative phosphorylation through elevated levels of substrates essential to activity of the TCA cycle and oxidative phosphorylation, such as pyruvate, ADP, and NADH [78].…”
Section: Pi3k-akt-mtor Signaling In Amlmentioning
confidence: 99%
“…Enhanced glycolysis has been observed in AML cell lines and in human primary AML blasts [10], while both the phosphoinositide 3-kinase (PI3K)/serine-threonine protein kinase B (AKT) and the mammalian target of rapamycin (mTOR) seemingly contribute to this glycolytic metabolism [11,12]. It has also been reported that AML patients have a distinct glucose metabolic signature as well as six serum metabolites involved in the glycolytic pathway which were identified and proposed as new prognostic biomarkers in the subgroup of patients with normal cytogenetics [13].…”
Section: Metabolic Reprogramming In Acute Myeloid Leukemiamentioning
confidence: 99%
“…Additionally, leukemic stem-cells (LSCs) might have a role in inducing insulin resistance and decreasing insulin secretion, in order to increase the supply of glucose to malignant cells, therefore inducing alterations of systemic physiology by co-opting systemic regulatory mechanisms in their favor [17]. Metabolic plasticity allows AML cells to balance between glycolysis and OXPHOS, however, these metabolic adaptations likely differ between AML sub-types [12] and also within leukemic cells from the same patient [18].…”
Section: Metabolic Reprogramming In Acute Myeloid Leukemiamentioning
confidence: 99%
See 1 more Smart Citation